Manipulation of Energy Transfer Processes in Nanochannels. (11th February 2010) - Devaux, André; Calzaferri, Gion
Abstract : The realisation of molecular assemblies featuring specific macroscopic properties is a prime example for the versatility of supramolecular organisation. Microporous materials such as zeolite L are well suited for the preparation of host-guest composites containing dyes, complexes, or clusters. This short tutorial focuses on the possibilities offered by zeolite L to study and influence Förster resonance energy transfer inside of its nanochannels. The highly organised host-guest materials can in turn be structured on a larger scale to form macroscopic patterns, making it possible to create large-scale structures from small, highly organised building blocks for novel optical applications.